PERAN SISTEM INFOMASI MANAJEMEN PENDIDIKAN (SIMDIK) DALAM MENINGKATKAN KUALITAS PENGELOLAAN PONDOK PESANTREN: STUDI LITERATUR REVIEW - Fadhil Ismail; Muhammad Rosyidi (STKIP Pesisir Selatan, 2026)
Digital transformation demands that Islamic boarding schools (pesantren) adopt Education Management Information Systems (EMIS) to strengthen governance. However, literature on this topic remains scattered and has not been systematically synthesized. This study aims to identify the role of EMIS in improving the management quality of pesantren and to map key themes, benefits, challenges, and future research agendas. Using the Systematic Literature Review (SLR) method with the PRISMA protocol, data were collected from Google Scholar, SINTA, and Scopus (2020–2025). From 118 initial articles, 11 relevant studies were selected for analysis through thematic synthesis. The results reveal seven primary themes regarding the role of EMIS: (1) educational administration management, (2) learning and infrastructure management, (3) financial and funding management, (4) student recruitment management, (5) technology-based service innovation, (6) information system policy and implementation, and (7) stakeholder acceptance and usage of EMIS. This synthesis demonstrates that EMIS significantly enhances efficiency, transparency, accountability, and data-driven decision-making. Nevertheless, implementation is still hindered by constraints in human resource competence, infrastructure, and cultural resistance.